DIFFERENTIAL EQUATION WITH POCHHAMMER POLYNOMIALS (x)n SOLUTIONS (x)1 TO (x)4 - Aboites, Vicente; Trejo García, David (IJRDO -JOURNAL OF MATHEMATICS, 2020)
In this paper we present a third order differential equation that has the Pochhammer polynomials from orders one through four as solutions. Obtaining this equation is useful to characterize the Pochhammer polynomials in a similar way to other families of special polynomials. We believe that an equation for higher orders is possible following the same methodology.